Online Education in the Post COVID-19 Era: Students' Perception and Learning Experience - Nastaran Peimani; Hesam Kamalipour (MDPI AG, 2021)
Students' learning experiences and perceptions are markedly influenced by the use of digital technology during the COVID-19 pandemic. Exploring students' perception of blended online learning, amid the adaptations of the higher education sector in the wake of uncertainty, has become more critical than ever. This paper reflects on the experience of learning and teaching the Research Methods and Techniques subject in the postgraduate programme of MA Urban Design at Cardiff University during COVID-19 in the UK. To do so, we designed and carried out an online survey to explore students' perception of online teaching and learning activities, feedback and assessment, and digital platforms based on their experience during the subject delivery period in the 2020-2021 academic year. One of the significant findings of this paper was that students agreed with the impact of eye contact on their virtual learning experience but as long as this was aligned with their rights to see others, including their peers and instructors, rather than reciprocal rights to be seen. In addition, students felt that facilitating synchronous communication through effective interaction among diverse peers has been quite challenging in small-group online reading seminars. The majority of respondents also reported that attending live online lectures was more helpful than watching pre-recorded lectures. Online formative feedback and synchronous interim reviews also allowed students to reflect on their progress and develop their projects further before their summative assessment. The outcomes of this paper can effectively assist educators who consider delivering programmes, adopting a blended online learning environment design model, in the post COVID-19 era. The findings of this study can also provide guidance for further developments and improvements in using digital technology and blended online learning in urban design education and pedagogy.